Preparation of aminoethyl glycosides for glycoconjugation - Šardzík, Robert; Noble, Gavin T.; Weissenborn, Martin J.; Martin, Andrew; Webb, Simon J.; Flitsch, Sabine L. (Beilstein Journal of Organic Chemistry, 2010)
The synthesis of a number of aminoethyl glycosides of cell-surface carbohydrates, which are important intermediates for glycoarray synthesis, is described. A set of protocols was developed which provide these intermediates, in a short number of steps, from commercially available starting materials.
Keywords: aminoethyl glycosides; glycoarrays; glycoconjugation; glycosylation